Optimalisasi Peran Masyarakat Lokal dalam Pengelolaan Sampah Pesisir melalui Program Bersih Pantai di Pantai Elak-Elak, Lombok Barat - Wiwid Andriyani Lestariningsih; Mahardika Rizqi Himawan; Sholihati Lathifa Sakina; Nurliah; Rhojim Wahyudi; Saptono Waspodo; Ibadur Rahman; Paryono; Chandrika Eka Larasati; Sadikin Amir; Soraya Gigentika; Edwin Jefri; Ayu Adhita Damayanti; Sitti Hilyana (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Plastic waste is a pollution problem in coastal areas, and this issue has become a global concern that requires serious attention, especially for archipelagic countries like Indonesia. This community service program aims to reduce plastic pollution at Elak-Elak Beach, West Lombok, and raise environmental awareness among the local community. Conducted in September 2023, the program involved the participation of nearly 200 students and 12 lecturers from the Marine Science Program at the University of Mataram, along with several local community members. Through scheduled beach clean-up activities, the program successfully collected approximately 10 bags, equivalent to 50-70 kg of waste, with plastic dominating the types of waste found. In addition to waste reduction efforts, the program also indirectly educated the local community about the impacts of plastic pollution on marine ecosystems, successfully increasing participants' awareness after the activities. Although the program showed positive results, challenges remain in waste management and the lack of adequate facilities. Therefore, ongoing collaboration between the community, government, and relevant organizations is essential to preserve Elak-Elak Beach and educate the public on the importance of proper environmental management.